Karakteristik Morfomeristik Ikan Betta schalleri Asal Pulau Bangka - Lista, Dona; Lindiantika, Lindiantika; Khanati, Olivia; Lestari, Eva; Syarif, Ahmad Fahrul (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Lista, D., Lindiatika, L., Khanati, O., Lestari, E., & Syarif, A.F. (2023). Morphomeristic characteristics of schalleri betta fish from Bangka Island. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 564-569). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Blue Tepalak/Tempalak fish (Betta schalleri) is a freshwater fish with potential as an ornamental fish which is in endangered conservation status (Endangered; EN). Until now, the existence of Betta schalleri fish in nature is thought to be increasingly difficult to find due to a decrease in habitat quality. This research aimed to examine the morphomeristic characteristics of the Schalleri Betta fish found in the waters of Bangka Island. Data collection for this research was located in the waters of Bencah Village, Air Gegas District, South Bangka Regenc. Information regarding the existence of the Betta schalleri’s natural habitat was obtained from the surrounding community. A total of 15 individual fish were successfully obtained from the research location. Fish samples showed meristic character D.II.8; P.11-12; V.I-II.4; A.II.24; C.13; LL.31. The morphometrics show a total length of 5,44 cm – 6, 20 cm, standard length 3,98 cm – 4,55 cm, head length 1,16 cm – 1,48 cm, head height 0,87 cm – 1,10 cm, and body height 1,04 cm – 1,28 cm. Based on the results of research on the meristic and morphomeristic identification of the schalleri betta fish, similarities were found to the schalleri betta fish described by Kottelat & Ng (1994). So it can add to the completeness of the morphomer data for schalleri betta fish from Bangka Island.